COVID-19 Pandemic – Implications, Planning, and Recommendations related to Dental Care Services and Dental Education - Fazal Ghani (Journal of Rawalpindi Medical College, 2020)
During the past few months, our understanding of the transmission, epidemiology, clinical symptoms, and management of Covid-19 has considerably improved. This had made the dental healthcare personnel confident enough and ready to provide safely by implementing efficient prevention and cross-infection control strategies in the dental clinical setting. , At the same time, it is necessary that we must be constantly aware of the continuation of such infectious threats challenging our infection control regimen and preparedness to provide dental treatments and teaching and education. Good infection prevention and control strategies need to be evidence-based and in line with the recommendations of the local and international public health agencies. The disruption in dental services and dental education all over the world resulted in this pandemic has emphasized and resulted in new, innovative and improved infection prevention and control strategies and adoption of alternative teaching, learning and assessment strategies for students. It further reinforces the need for continued research exploring ways for responding better to future contagious disease threats.